Prospects of the air-shower radio array at the Tien Shan high-altitude scientific station - Bezyazeekov, P.A.; Fedorov, O.; Kostunin, D. (Recent Contributions to Physics, 2021)
High energy astrophysics has been actively developed since the last decades. The photons and neutrinos produced at astrophysical sources were detected up to energies of PeV, while the measured spectrum of cosmic rays lasts from GeV to ZeV energies. The challenges of modern detectors are not only pushing towards higher energies to reach the cosmic acceleration limit, but also increasing the resolution of the reconstruction of the energy, arrival direction and the type of the cosmic particle. Due to low flux of these particles, their detection is feasible only by measurement of air-showers, atmospheric cascades of secondary particles induced by the primary one. One of the promising methods of the air-shower detection is the sparse digital radio arrays, a young, but cost-effective technique aimed at the cosmic particles with energies beyond PeV. The future detectors aimed at detection of cosmic rays, photons and neutrinos of extreme energies are based on the antenna arrays located either in ice or on mountain slopes. The latter are sensitive both to downward-directional air-showers induced by cosmic rays, and upward-going ones produced by skimming neutrinos interacting with rock. The prototyping of such an array requires appropriate location (high-altitude mountains) with corresponding infrastructure and ideally additional cosmic-ray detector for the cross-calibration of antennas. The-Tien Shan High-altitude Scientific Station (TSHSS) located near Almaty, Kazakhstan, and equipped with air-shower instruments, is an ideal place for this prototype. In this work we discuss the prospects of the radio technique, its current challenges and report the recent advances of the prototype radio installations at TSHSS.